Melatonin promotes sirtuin 1 expression and inhibits IRE1α–XBP1S–CHOP to reduce endoplasmic reticulum stress–mediated apoptosis in chondrocytes - Qin, Kunpeng; Tang, Hao; Ren, Yi; Yang, Di; Li, Yetian; Huang, Wei; Wu, Yunfeng; Yin, Zongsheng (Frontiers in Pharmacology, 2022)
Osteoarthritis (OA) is the most common chronic disease characterized by a loss of chondrocytes and the degeneration of cartilage. Inflammation plays an important role in the pathogenesis and progression of OA via the activation of the endoplasmic reticulum (ER) stress signaling pathway. In this study, we stimulated human primary chondrocytes with lipopolysaccharide (LPS) to reduce cell viability and induce chondrocyte apoptosis. LPS–stimulated human primary chondrocytes induced ER stress and significantly upregulated the ER chaperone glucose–regulated protein 78 (GRP78) and increased the expression level of C/EBP–homologous protein (CHOP), a key mediator of ER stress––induced apoptosis. Interestingly, melatonin treatment attenuated ER stress–mediated chondrocyte apoptosis. Melatonin inhibited the expression of cleaved caspase-3, cleaved caspase-10, Bax, CHOP, GRP78, cleaved caspase-4, phospho–inositol–requiring enzyme 1α (P-IRE1α), and spliced X-box-binding protein 1 (XBP1S). In an anterior cruciate ligament transection mouse model of OA, melatonin (50 and 150 mg/kg) dose–dependently relieved joint cartilage degeneration and inhibitied of chondrocyte apoptosis. Immunohistochemical analysis indicated that melatonin could promote SIRT1 the expression and inhibit CHOP and cleaved caspase-3 expression in OA mice. In conclusion, our findings demonstrate for the first time that melatonin inhibits the IRE1α-XBP1S-CHOP signaling pathway by promoting the expression of SIRT1 in LPS-treated human chondrocytes and delaying OA progression in vivo.